2007
DOI: 10.1007/s10693-007-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Diversification Improve the Performance of German Banks? Evidence from Individual Bank Loan Portfolios

Abstract: Should banks be diversified or focused? Does diversification indeed lead to enhanced performance and, therefore, greater safety for banks, as traditional portfolio and banking theory would suggest?This paper investigates the link between banks' profitability (ROA) and their portfolio diversification across different industries, broader economic sectors and geographical regions measured by the Herfindahl Index. To explore this issue, we use a unique data set of the individual bank loan portfolios of 983 German … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 26 publications
8
52
0
Order By: Relevance
“…Our results support the finding of Nguyen et al, (2015) and Saunders et al, (2014). However, these findings are different from the work of Hayden et al, (2007) and Stiroh (2006a, b).…”
Section: Diversification and Bank Performancesupporting
confidence: 83%
“…Our results support the finding of Nguyen et al, (2015) and Saunders et al, (2014). However, these findings are different from the work of Hayden et al, (2007) and Stiroh (2006a, b).…”
Section: Diversification and Bank Performancesupporting
confidence: 83%
“…Lepetit et al [10] found that there was a positive relationship between fee-based activities (commission income, which is a type of non-interest income) and solvency risk based on the data of European banks from 1996 to 2002. Hayden et al [11] showed that, for most German banks, a higher level of diversification may result in a lower return, by using data of the loan portfolios of banks during the 1996-2002 period. Using data pertaining to banking in the USA from 1997 to 2002, Stiroh [12] analyzed the influence of income diversification on bank performance, and found that decreased interest income volatility contributed to income stability, while non-interest income was more volatile than interest income.…”
Section: The Income Diversification Of Banksmentioning
confidence: 99%
“…A large theory literature examines the role of physical distance and information in banking competition (Sharpe, 1990, Rajan, 1992, Dell'Ariccia and Marquez, 2004, 5 Acharya, Hasan and Saunders (2006, using Italian bank-level data and exposure to 21 industry categories, finds that sectoral concentration increases returns and reduces risk, but only for high-risk banks (those with many doubtful or non-performing loans). Hayden, Porath and Westernhagen (2007), using German bank-level data and exposure across 23 sectors, also finds that concentration generally improves returns and loan performance. Similarly, Boeve, Duellmann and Pfingsten (2010) and Jahn, Memmel and Pfingsten (2016), using German bank-level data, find that sectoral specialization leads to better monitoring and fewer write-offs.…”
mentioning
confidence: 88%